AKULTURASI ETNIS TIONGHOA DI DESA LANGGAHAN, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Hartati Dwijayanti, Ni Kadek Wira; Kebayantini, Ni Luh Nyoman; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Acculturation is a social process in which a certain group adopt new and different cultural elements. This study used a qualitative approach with a descriptive-explanative type and it implemented AGIL (Adaptation, Goal-attainment, Integration, and Latency) theory by Talcott Parsons. It examined the acculturation of Chinese and Balinese culture in Langgahan Village since the period of the Balingkang kingdom in Bangli. This study also examined the forms of Chinese’s acculturation during Odalan Kongco and Odalan Pura Dalem, Imlek, Galungan and Kuningan, as well as the existence of Sanggah and Nyolo buildings in every Chinese’s house. Keywords: Acculturation, Chinese Ethnicity, AGIL, Langgahan Village